1993
DOI: 10.1557/proc-324-353
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Substrate Temperature Measurement During MBE by Band-Edge Reflection Spectroscopy

Abstract: The use of band-edge reflection spectroscopy (BRS) to determine the substrate temperature during MBE is reviewed. Data are presented for Si, GaAs, InP and CdZnTe substrates, and the use of BRS during the growth of ZnTe on Si is demonstrated. We discuss complications that arise due to optical interference in the epitaxial layers, and methods to compensate for the effects of interference are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…The samples were heated at 10°C/min with interruptions of on the order of 1 min at key temperatures where RHEED and/or reflectance data were collected. The reflectance data were obtained using a commercial instrument which utilizes the shift in absorption band edge as a function of temperature characteristic of a semiconductor 16 to calibrate the temperature of the substrate once the Sb multilayer had desorbed. We have found that the actual sample temperature and that measured by the thermocouple agree to within 7°C.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were heated at 10°C/min with interruptions of on the order of 1 min at key temperatures where RHEED and/or reflectance data were collected. The reflectance data were obtained using a commercial instrument which utilizes the shift in absorption band edge as a function of temperature characteristic of a semiconductor 16 to calibrate the temperature of the substrate once the Sb multilayer had desorbed. We have found that the actual sample temperature and that measured by the thermocouple agree to within 7°C.…”
Section: Methodsmentioning
confidence: 99%
“…Another implementation of in situ band gap determination, is to bring white light in the pyrometer port and measure the band-edge reflection spectroscopy using the backreflected light coming out of the pyrometer viewport. 32 This method works well for bare substrates but suffers from optical interference effects, especially when the films are smooth and uniform in thickness (precisely what one wants to achieve with MBE).…”
Section: Difficulties In Determining the Substrate Temperature Withinmentioning
confidence: 99%
“…The substrate temperature sensor relies on the method of absorption-edge spectroscopy, 15,18 conducted in reflection mode, to sense the bandgap, and hence temperature, of a 2 cm x 2 cm Si "witness" wafer that is conductively mounted on the back side of the substrate mounting block. 9,16 This measurement technique requires optical access to the backside of the substrate mounting block, which is provided in our MBE systems via a linear quartz light pipe installed on a single-axis manipulator.…”
Section: Hgcdte Mbe System Sensorsmentioning
confidence: 99%
“…Sensors developed for HgCdTe alloy composition, [9][10][11][12]14 substrate temperature, 15 and source fluxes 16 enable the growth process to be monitored and, in many cases, controlled using closed-loop feedback control paradigms. This approach can substantially increase the yield of grown layers that meet target specifications for optical properties and crystallographic defects and dramatically shorten the time required for establishment and qualification of new growth processes.…”
Section: Introductionmentioning
confidence: 99%